Pengaruh Content Marketing, Citra Merek, Kualitas Pelayanan dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada E-Commerce Tokopedia: Studi pada Pengguna di Purwokerto - Widyaningtyas, Dian; nurazizah, afifah; Justiana Astuti, Herni; Endratno, Hermin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of content marketing, brand image, service quality, and consumer trust on purchasing decisions of Tokopedia e-commerce users in Purwokerto. The research used a quantitative approach. The population in this study were Purwokerto residents who are Tokopedia users. The sampling method used was Purposive sampling, namely respondents based on criteria, in this case the selected respondents were Tokopedia users who live in Purwokerto, and have made transactions on Tokopedia at least once. A sample of 110 respondents was determined using the Lemeshow formula, data were collected through a questionnaire with a five-point Likert scale, and analyzed using multiple linear regression to test the influence of each independent variable on purchasing decisions. The study shows that all independent variables have a positive effect on purchasing decisions. This study confirms that an effective content marketing strategy, strengthening brand image, improving service quality, and building consumer trust are very important in increasing purchasing decisions on the Tokopedia e-commerce platform.